Maintaining sexual health in commercial sex workers in Australia: condom effectiveness, screening, and management after acquiring sexually transmissible infections - P. Heather Lyttle; Sandra C. Thompson (Elsevier, 2004)
Abstract Objective:To provide practical advice to health care providers and public health practitioners regarding screening and management of sexually transmitted infections (STIs) in sex workers, and to examine the effectiveness of condoms in reducing transmission of STIs. Methods:Medline search using the key words sex workers, prostitutes, condoms and these terms in conjunction with pregnancy, sexually transmitted infections (including the names of individual STIs), infectivity, exclusion periods. Additional articles were identified from cited references. Articles were selected on the basis of information provided on efficacy of condoms in STI prevention, prevalence of STIs in sex workers and changes following condom promotion, and advice about management of STIs in infected workers. Results:Condoms offer some protection (30-90%) against STIs passed in semen, urethral, vaginal or cervical secretions (such as HIV, gonorrhoea, chlamydia). They give little to no protection (0-30%) against diseases due to skin‐to‐skin contact such as genital herpes and genital warts. Transmissibility of STIs varies according to the sex of the exposed person and the sexual practice. Condom effectiveness against STIs also varies with gender, and experience and consistency of condom use. Conclusions:Sex workers require regular screening for STIs as condom use is not fully protective. Management of sex workers identified with infection requires understanding of the issues faced by sex workers, biological characteristics of the infective organism, treatment efficacy, and test sensitivity and specificity. Advice on frequency of STI testing, supply of medical certificates, management of condom breakage, and management of infected sex workers is proposed.